Intraluminal colonization into the seminiferous tubules in mice - Guzmán-Masias, Luis (2010)
Using the primordial germ cells transplant technique, we could be able preserve and multiply pluripotent cells in the receptor for a long period of time. In this work, We aim to evaluate intraluminal colonization of a cellular gonocyte suspension from 14.5 dpc fetus. Cellular suspension with PGC's were isolated from fetus male mice by two enzymatic digestion steps, and cellular suspensions were transplanted into the rete testis of the receptor animals that were previously injected with Busulfan to decrease their own spermatogenesis. In this research the intraluminal colonization was identified in 13.27%, demonstrating that transplantation of a cellular suspension from gonocytes of fetus of 14.5 dpc containing PGCs can colonize the seminiferous tubules and support the spermatogenesis.